Effekter av mentaliseringbaserad terapi i en skånsk kohort - Eriksson Granborn,Gunnar; Magnusson,Emma (2024)
The aims of this quality assurance study were to a) describe the cohort with borderline personality disorder (BPD) who underwent Mentalization-based Treatment (MBT) at the psychiatric out-patient unit Mottagning emotionell instabilitet in Malmö, and to b) evaluate treatment effects. Data were collected through systematic search of psychiatric medical records regarding 86 patients who completed treatment between the years 2011 and 2024. Women constituted 92% of the cohort, whose mean age at start of treatment was 31,20 years, and the mean number of registered co-occuring psychiatric diagnoses were seven. Primary outcome measures showed significantly lower symptom rates post-treatment on self-report measures SCL-90 and SCID-II-PQ. Number of patients meeting criteria for BPD in clinical assessment were significantly lower at end of treatment. Secondary outcome measures showed significantly lower rates of psychiatric emergency care use. No significant change regarding inpatient service use were noted for either number of events or days of inpatient care. Nevertheless, in absolute terms, number of inpatient care days dropped considerably during and post- as compared to pre-treatment. This drop was especially marked for a sub-group, whose pre-treatment inpatient service use was particularly high. No significant change regarding rates of certified sick leave were noted. Post-treatment, 35% of patients were referred to primary care. This study indicates MBT as an effective treatment for BPD-patients in psychiatric care in Malmö. Further implementation of MBT teams in other psychiatric areas within Region Skåne is recommended.
Keywords: Borderline/emotionellt instabilt personlighetssyndrom (BPD/EIPS); mentaliseringsbaserad terapi (MBT); gruppterapi; individualterapi; SCL-90; kvalitetssäkring; behandlingsutvärdering